Effects of Hypoxia and Bed Rest on Markers of Cardiometabolic Risk: Compensatory Changes in Circulating TRAIL and Glutathione Redox Capacity - Biolo, Gianni; Di Girolamo, Filippo G.; McDonnell, Adam; Fiotti, Nicola; Mearelli, Filippo; Situlin, Roberta; Gonelli, Arianna; Dapas, Barbara; Giordano, Mauro; Lainscak, Mitja; Grassi, Gabriele; Zauli, Giorgio; et al. (Frontiers in Physiology, 2018)
In chronic diseases, hypoxia and physical inactivity are associated with atherosclerosis progression. In contrast, a lower mortality from coronary artery disease and stroke is observed in healthy humans residing at high altitude in hypoxic environments. Eleven young, male volunteers completed the following 10-day campaigns in a randomised order: hypoxic ambulatory, hypoxic bed rest and normoxic bed rest. Before intervention, subjects were evaluated in normoxic ambulatory condition. Normobaric hypoxia was achieved in a hypoxic facility simulating 4000 m of altitude. Following hypoxia, either in bed rest or ambulatory condition, markers of cardiometabolic risk shifted towards a more atherogenic pattern consisting of: (a) lower levels of total HDL cholesterol and HDL2 sub-fraction and decreased hepatic lipase; (b) activation of systemic inflammation, as determined by C-reactive protein and serum amyloid A; (c) increased plasma homocysteine; (d) decreased delta-5 desaturase index in cell membrane fatty acids, a marker of insulin sensitivity. Bed rest and hypoxia additively decreased total HDL and delta-5 desaturase index. In parallel to the pro-atherogenic effects, hypoxia activated selected anti-atherogenic pathways, consisting of increased circulating TNF-related apoptosis-inducing ligand (TRAIL), a protective factor against atherosclerosis, membrane omega-3 index and erythrocyte glutathione availability. Hypoxia mediated changes in TRAIL concentrations and redox glutathione capacity (i.e., GSH/GSSG ratio) were greater in ambulatory conditions (+34±6% and +87±31%, respectively) than in bed rest (+17±7% and +2±27% respectively). Hypoxia-induced cardiometabolic risk is blunted by moderate level of physical activity as compared to bed rest. TRAIL and glutathione redox capacity may contribute to the positive interaction between physical activity and hypoxia.